Splintering (sub) urbanism and social differences: Gated communities as the driver for suburban change in Chacras de Coria (Mendoza, Argentina) - Roitman, Sonia (Revista INVI, 2017)
This article analyses the geographical, economic and spatial transformations in suburbia as a consequence of the arrival of gated communities. The latter are fostering splintering (sub) urbanism, changes in land use and increasing spatial and social inequalities. The article provides evidence supporting this argument through the examination of the transformations occurring in Chacras de Coria, a suburb in the Metropolitan Area of Mendoza (MAM), Argentina. The analysis is based on primary and secondary data.